THE STUDENTS' PERCEPTION ON LEARNING USING ONLINE METHOD IN PANDEMIC ERA - Rahmi Aulia Nurdini; Imtihan Hanim (The Seall Journal, 2020)
The study is investigating the perceptions of students about learning using onlinemethod, the problems they encountered during e-learning process and theirstrategy to face e-learning method. The subject of the research was coming from 4students who were divided into third and fifth semester from 2 universities, suchas Bina Sarana Informatika and Muhammadiyah Tangerang University. Thedescriptive qualitative is used to gather the required data. Five questions areasked to get the data through online interview. Data shows that most of thestudents’ perceptions on online learning method is quite similar. Most of thestudents feel the same problems which relate to internet connection problems. Theproblem distracted their understanding of the materials given by the lecturers.Then, the strategy to encounter the problems are asking and discussing withfriends. Besides, they also find their own way through internet. Despite of beingeasy to find many ways to solve the problems, the offline method becomes theirmost favourable learning method.